Mechanical confinement via a PEG/Collagen interpenetrating network inhibits behavior characteristic of malignant cells in the triple negative breast cancer cell line MDA.MB.231. (1st September 2018) - Reynolds, Daniel S.; Bougher, Kristen M.; Letendre, Justin H.; Fitzgerald, Stephen F.; Gisladottir, Undina O.; Grinstaff, Mark W.; Zaman, Muhammad H.
Graphical abstract: Abstract: To decouple the effects of collagen fiber density and network mechanics on cancer cell behavior, we describe a highly tunable in vitro 3D interpenetrating network (IPN) consisting of a primary fibrillar collagen network reinforced by a secondary visible light-mediated thiol-ene poly(ethylene glycol) (PEG) network. This PEG/Collagen IPN platform is cytocompatible, inherently bioactive via native cellular adhesion sites, and mechanically tunable over several orders of magnitude—mimicking both healthy and cancerous breast tissue. Furthermore, we use the PEG/Collagen IPN platform to investigate the effect of mechanical confinement on cancer cell behavior as it is hypothesized that cells within tumors that have yet to invade into the surrounding tissue experience mechanical confinement. We find that mechanical confinement via the IPN impairs behavior characteristic of malignant cells (i.e., viability, proliferation, and cellular motility) in the triple negative breast cancer cell line MDA.MB.231, and is more effective than removal of soluble growth signals. The PEG/Collagen IPN platform is a useful tool for studying mechanotransductive signaling pathways and motivates further investigation into the role of mechanical confinement in cancer progression. Statement of Significance: In this study, we have developed, optimized, and applied a novel 3D in vitro cell culture platform composed of an interpenetrating network (IPN) that is both mechanically tunable and inherently bioactive. The IPN consists of a primary fibrillar collagen type-1 network reinforced by a secondary thiol-ene poly(ethylene glycol) (PEG) network. The IPNs are formed via a novel strategy in which cell-laden collagen gels are formed first, and soluble PEG monomers are added later and crosslinked via visible light. This approach ensures that the collagen gels contain a fibrillar architecture similar to the collagen architecture present in vivo. We applied our IPN platform to study the effect of mechanical confinement on cancer cell behavior and found that it inhibits malignant-like behavior.